DYNAMIC STABILITY OF CIRCULAR THIN AND THICK PLATES ON ELASTIC FOUNDATION (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
This paper studies the dynamic buckling of thin and thick circular and annular plates on elastic foundation subject to nonconservative forces. The initial elastic, geometric stiffness and mass matrices are obtained using the Rayleigh-Ritz method. The approximation functions for displacements are polynomials in the radial direction combined with trigonometric functions in the circumferential direction, enriched by higher order polynomials without inclusion of additional nodes. The effect of load displacement dependence is introduced in the so-called load matrices, which are obtained from equilibrium considerations in the case of nonconservative behavior. The model was implemented in MAPLE. The examples present comparisons illustrating the effect of shear deformation, rotatory inertia and elastic foundation on flutter loads.